An Observational Study of the First Experience with Bevacizumab for the Treatment of Patients with Recurrent High-Grade Glioma in Two Belgian University Hospitals. (13th March 2012) - Huylebrouck, M.; Lv, S.; Duerinck, J.; Van Binst, A.; Salmon, I.; De Greve, J.; De Witte, O.; Luce, S.; Michotte, A.; D'Haens, J.; Neyns, B.
Abstract : Background . Bevacizumab (BEV), a humanized immunoglobulin G1 monoclonal antibody that inhibits VEGF has demonstrated activity against recurrent high-grade gliomas (HGG) in phase II clinical trials. Patients and Methods . Data were collected from patients with recurrent HGG who initiated treatment with BEV outside a clinical trial protocol at two Belgian university hospitals. Results . 19 patients (11 M/8 F) were administered a total of 138 cycles of BEV (median 4, range 1–31). Tumor response assessment by MRI was available for 15 patients; 2 complete responses and 3 partial responses for an objective response rate of 26% for the intent to treat population were observed on gadolinium-enhanced T1-weighted images; significant regressions on T2/FLAIR were documented in 10 out of 15 patients (67%). A reduced uptake on PET was documented in 3 out of 4 evaluable patients. The six-month progression-free survival was 21% (95% CI 2.7–39.5). Two patients had an ongoing tumor response and remained free from progression after 12 months of BEV treatment. Conclusions . The activity and tolerability of BEV were comparable to results from previous prospective phase II trials. Reduced uptake on PET suggests a metabolic response in addition to an antiangiogenic effect in some cases with favorable clinical outcome.